A model for degassing at the Soufriere Hills Volcano, Montserrat, West Indies, based on geochemical data - Edmonds, M; Pyle, D; Oppenheimer, C (2001)
A model is presented to describe the degassing behaviour of sulphur and chlorine at the Soufrière Hills Volcano, Montserrat, using both geochemical analyses of glass and remote sensing data (correlation spectroscopy and open-path Fourier transform infrared spectroscopy). Constraints on total SO 2 emitted at the surface (1.2 Mt up to September 2000) and petrological data indicate that the andesite was not the sulphur source. Mafic magma that intruded into the andesite magma chamber to trigger eruption at 5-7 km depth recharged the sulphur contents of the shallow volcanic system. Sulphur is removed from the mafic melt to enter a water-dominated vapour phase at depths of 5-7 km or greater. The passage of SO 2 to the surface is sporadic and discontinuous in time and is governed by the permeability of the conduit and wallrock and the supply of mafic magma from depth. Chlorine is derived from the andesite magma and degasses on magma ascent, shown by the melt evolution recorded in the matrix glasses and the apparent link between extrusion rate and HCl flux at the surface. Petrological estimates of chlorine loss agree with measurements of total chlorine emission at the surface. The chlorine content of the matrix glass may be explained by fractional crystallisation combined with the partitioning of chlorine into a water-rich fluid phase with a partition coefficient of the order of 50. © 2001 Elsevier Science B.V. All rights reserved.